The Role of Social Media in Influencing Tourist Travel Decisions: A Systematic Literature Review - Mardiah , fahmi; Faridah , Anni (Academia Open, 2026)
General Background: The rapid growth of digital technology has transformed the tourism industry, positioning social media as a primary source of travel information. Specific Background: Social media enables users to share experiences through user-generated content, reviews, and visual media, which are widely used in destination evaluation and travel planning. Knowledge Gap: Previous studies present inconsistent findings due to variations in research focus, methods, and contexts, indicating the need for a comprehensive synthesis. Aims: This study aims to systematically examine the role of social media in shaping tourist travel decision processes using a Systematic Literature Review approach. Results: Based on 22 Scopus-indexed articles selected through the PRISMA framework, findings indicate that social media plays a central role in information searching, destination image formation, travel intention, and final decision-making, driven by user-generated content, detailed reviews, visual elements, and online interactions. Novelty: This study provides an integrated synthesis of diverse empirical findings, offering a structured understanding of how social media contributes to multiple stages of tourist decision-making. Implications: The results highlight the importance of social media as a strategic tool in tourism marketing and suggest the need for future research to expand databases, timeframes, and contextual diversity. Highlights• Social media serves as a primary information source in travel planning• User-generated content shapes destination perception and tourist intention• Online interactions contribute to final travel decision-making stages KeywordsSocial Media; Travel Decision; User Generated Content; Destination Image; Systematic Literature Review